2020
DOI: 10.1038/s41550-020-1051-1
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer’s perspective of polycyclic aromatic hydrocarbons in galaxies

Abstract: Polycyclic aromatic hydrocarbon (PAH) molecules, as revealed by the distinctive set of emission bands at 3. 3, 6.2, 7.7, 8.6, 11.3 and 12.7 µm characteristic of their vibrational modes, are abundant and widespread throughout the Universe. They are ubiquitously seen in a wide variety of astrophysical regions, ranging from planet-forming disks around young stars to the interstellar medium (ISM) of the Milky Way and external galaxies out to high redshifts at z > ∼ 4. PAHs profoundly influence the thermal budget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(103 citation statements)
references
References 178 publications
(289 reference statements)
3
100
0
Order By: Relevance
“…Potential building blocks that did not participate in water chemistry were excluded. This scenario explains the exclusion of various molecules from extant biochemistry, such as polycyclic aromatic hydrocarbons, which are highly abundant in the abiotic universe (Hertzog et al 2019 ; Li 2020 ), but do not react with water.…”
Section: Discussionmentioning
confidence: 99%
“…Potential building blocks that did not participate in water chemistry were excluded. This scenario explains the exclusion of various molecules from extant biochemistry, such as polycyclic aromatic hydrocarbons, which are highly abundant in the abiotic universe (Hertzog et al 2019 ; Li 2020 ), but do not react with water.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed Spitzer IRS spectra of hundreds of galaxies with AGN activity found that some PAH features are seen in most cases, 146 showing that PAHs can survive in some of these environments. Li 147 summarized the PAH observations in AGN by noting that the 6.2, 7.7, and 8.6 μm PAH features, although suppressed with respect to the 11.3 μm band (perhaps because smaller PAHs are more susceptible to the hard radiation field of an AGN) nevertheless can be present. Figure 5 in Ref.…”
Section: Gep-i Redshift Measurementsmentioning
confidence: 99%
“…Other physical effects will also influence the strengths of these mid-IR PAHs features, for example, low metallicity in high-z, young galaxies, or destructive supernovae activity. 147 Although weak PAH features make photometric redshift measurements more challenging, it is precisely the complexity and variability of these features that ultimately enable diagnosis of the physical conditions present.…”
Section: Gep-i Redshift Measurementsmentioning
confidence: 99%
“…These forces bring SP3-bond. In interstellar space, central star can do such illumination on cosmic dust 29) . By photoionization, angle of 1C-0C-2C varies from 94.7 to 95.4 degree.…”
Section: S Sp Pi In N S St Ta At Te E a An Na Al Ly Ys Si Is Smentioning
confidence: 99%